Active labour market policies and youth employment in European peripheries - Simões, F.; Tosun, J. (Politics and Governance, 2024)
This thematic issue discusses the design, implementation, and impact of youth-oriented active labour market policies in Europe, with a particular emphasis on its peripheries. The need to address territorialised, youth-oriented active labour market policies is pressing for several reasons. For one, the whole socioeconomic paradigm is undergoing fundamental changes due to the dual transition (digital and green) that is expected to have an impact on the rural/urban divide. Moreover, at the subnational level, youth unemployment in certain regions is a more pressing problem than suggested by existing studies, which have mostly focused on the national level. This implies that closer inspection of the subnational level, in general, and the peripheral regions, in particular, will reveal more marked cross-national differences. This thematic issue offers a point of departure for the suggested territorialised approach to the study of how active labour market policies for young people are formulated and implemented, and which effects they have on their target groups.